2009
DOI: 10.1086/597578
|View full text |Cite
|
Sign up to set email alerts
|

The Expansion of the Microbiological Spectrum of Brain Abscesses with Use of Multiple 16S Ribosomal DNA Sequencing

Abstract: Background. Brain abscess is commonly treated using empirically prescribed antibiotics. Thus, a comprehensive study of bacterial organisms associated with brain abscess is essential to define the best empirical treatment for this life-threatening condition. Methods. We prospectively compared cultures to single and multiple sequenced 16S ribosomal DNA polymerase chain reaction amplifications (by cloning and/or pyrosequencing) of cerebral abscesses in 20 patients from 2 hospitals in Marseilles, France, during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
85
1
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(96 citation statements)
references
References 44 publications
3
85
1
7
Order By: Relevance
“…Campylobacter gracilis (previously Bacteroides gracilis) and Campylobacter rectus are the most dominant Campylobacter species in the oral cavity and represent another long-acknowledged genus in intracranial infections rarely recovered by culture (1,4,30). In this study, C. gracilis (n ϭ 8) was found exclusively in samples positive for Actinomyces spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Campylobacter gracilis (previously Bacteroides gracilis) and Campylobacter rectus are the most dominant Campylobacter species in the oral cavity and represent another long-acknowledged genus in intracranial infections rarely recovered by culture (1,4,30). In this study, C. gracilis (n ϭ 8) was found exclusively in samples positive for Actinomyces spp.…”
Section: Discussionmentioning
confidence: 99%
“…Recent investigations of bacterial brain abscesses using universal amplification of the bacterial 16S rRNA gene, followed by Sanger sequencing of cloned amplicons, have revealed that only a fraction of the bacteria present are identified by culture (1,2). Nevertheless, this approach has limitations when it comes to detecting smaller subpopulations in a multispecies community, unless very high numbers of clones are sequenced (3).…”
mentioning
confidence: 99%
“…The number of newly described bacteria has risen impressively during the past few decades (1,2). Notably, the identification of new pathogens in clinical microbiology has been spectacularly improved during previous decades by the use of molecular identification, especially 16S rRNA gene sequencing (3)(4)(5)(6)(7)(8). Molecular identification is one of the most useful techniques but remains expensive and requires a workload that is not adapted for routine use.…”
mentioning
confidence: 99%
“…A review of the literature confirms the role of Campylobacter gracilis in certain extra-oro-intestinal abscesses and empyemata (6,11). Most recently, it was discovered by broad-range amplification and cloning in three polybacterial brain abscesses (1). The blood culture results were included mainly to get a comparison between culture and sequencing, unaffected by antibiotics, sample collection procedures, or transportation.…”
Section: Discussionmentioning
confidence: 99%